Strategies and actions for academic underperformance in CURN - Bernal Payares, Omaira; Cifuentes Cifuente, Omar; Yances Cordoba, Lorenzo (Universidad Francisco de Paula Santander, 2015)
The present research focused on analyzing the academic performance of students who have not been able to reach the minimum required levels. Academic performance is explained by variables such as: habits, methods, study techniques and aptitude. The low academic performance is a level in which a student is when he/she obtains an average lower than 3.0 over 5.0 and is caused by learning difficulties, bad habits, absence of study techniques and methods and deficiencies in some areas, mainly in quantum and reading-writing. For the above mentioned, it is necessary to carry out an investigation that allows to know this situation and from there, to propose strategies and actions to overcome this situation and to show its commitment with the academic quality of the Business Administration Program of the Corporación Universitaria Rafael Núñéz 1P2012.